Disease profile of sheep and goats in Tiruchirapalli District of Tamil Nadu - Arya, S N; Mathur, D C; Bhatia, D K (The Indian Journal of Animal Sciences, 2012)
The disease profile of sheep and goats in Tiruchirapalli district of Tamil Nadu is highlighted from sample survey data. The sample was drawn by stratified two-stage simple random sampling without replacement. Two parameters, viz. disease prevalence rate (DPR) and case fatality rate (CFR) were used us measures of the intensity of disease infliction among the ruminants. Further, relative frequencies of various diseases were obtained separately for each category of the animals. The proportions of cases treated, recovered, died and disposed were also worked out. The DPR was 6% in sheep and 8% in goats; lambs and kids having the higher rates of 8% and 12% respectively. The CFR was over 60% in sheep and around 40% in goats. Prominent among the various ailments were enteritis, sheep/goat pox and pneumonia. Enteritis was conspicuous for the lion’s share in the disease infections. While a good proportion of the animals had received treatment and recovered, very high proportionate mortality was noticed among the untreated cases.